2013
DOI: 10.1002/etc.2351
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent snapshot of pharmaceuticals and pesticides in the river Meuse basin

Abstract: The river Meuse serves as a drinking-water source for more than 6 million people in France, Belgium, and The Netherlands. Pharmaceuticals and pesticides, both designed to be biologically active, are important classes of contaminants present in this river. The variation in the presence of pharmaceuticals in time and space in the Dutch part of the Meuse was studied using a multicomponent analytical method for pharmaceuticals combined with univariate and multivariate statistical analyses of the results. Trends an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The NSAIDs, including ibuprofen, diclofenac, fenoprofen, and acetaminophen, were generally higher in winter and the wet season, particularly acetaminophen, with p<0.01. The higher NSAIDs in the estuary were also observed in the previous study [31], which might be due to the higher usage in the winter seasons [33]. Our previous study showed that lower PPCP concentrations were observed in the wet season in Jiulong River compared to the dry season and normal season due to the rainfall dilution [9].…”
Section: Seasonal Variationsmentioning
confidence: 48%
“…The NSAIDs, including ibuprofen, diclofenac, fenoprofen, and acetaminophen, were generally higher in winter and the wet season, particularly acetaminophen, with p<0.01. The higher NSAIDs in the estuary were also observed in the previous study [31], which might be due to the higher usage in the winter seasons [33]. Our previous study showed that lower PPCP concentrations were observed in the wet season in Jiulong River compared to the dry season and normal season due to the rainfall dilution [9].…”
Section: Seasonal Variationsmentioning
confidence: 48%
“…The average recovery was 91 ± 14%. A detailed description of the method and its validation is given in Houtman et al . Detection limits using POCIS passive sampling were approximately 0.01 ng/L water.…”
Section: Methodsmentioning
confidence: 99%
“…The average recovery was 91 AE 14%. A detailed description of the method and its validation is given in Houtman et al [16]. Detection limits using POCIS passive Field feasibility bioanalytical SIMONI hazard identification Environ Toxicol Chem 36, 2017 sampling were approximately 0.01 ng/L water.…”
Section: Chemical Analyses and Sample Cleanupmentioning
confidence: 99%
“…Later studies of different parts of the Rhine and Meuse rivers reported similar pharmaceuticals 50,51 , however, in some studies the anti-diabetic drug metformin and its TP guanylurea were found to be the most abundant pharmaceutical in surface water samples. 50,52,53 While metformin was also quantified in this study, the median concentration only ranks 44 th over both years among the pharmaceuticals found. Higher levels of the anti-diabetic drug sitagliptin, th most abundant, were detected in Luxembourg.…”
Section: Spatio-temporal Distribution Of Pharmaceuticals Inmentioning
confidence: 69%